Enhancing hydrogen evolution reaction using transition metal atoms on 6,6,12-graphyne: A DFT study - Motaghi Fatemeh; Mohammadi-Manesh Hossein (Journal of the Serbian Chemical Society)
The escalating global population and the urgent need for sustainable energy solutions with minimal environmental impact have underscored the significance of developing renewable energy sources. Hydrogen, as an energy carrier and fuel, presents substantial advantages over other energy forms, alongside diverse applications in medical treatments and the production of critical chemicals like methane and methanol. Thus, hydrogen emerges as a potential alternative to fossil fuel, offering a stable and clean energy solution. In this study, we present a theoretical design of transition metal (TM) anchored 6,6,12- graphyne (GY) based catalysts for the hydrogen evolution reaction (HER) using density functional theory (DFT). Our findings reveal that among all evaluated systems, cobalt single-atom catalyst (SAC) anchored on 6,6,12-graphyne exhibit the highest thermodynamic stability and superior HER catalytic performance, with a remarkably low ΔGH* value of 0.042 eV. We have investigated the density of states, HOMOs, LUMOs, electron density and band structures of our designed SACs. This work provides a practical strategy for experimental groups to effectively tune the electronic structures of catalysts and enhance their catalytic activity.